Summarizing and paraphrasing as core strategies for enhancing reading comprehension and critical thinking: A literature review - Ni Wayan Sadiyani; Ida Bagus Artha Adnyana; Zanyar Nathir Ghafar; Nadia Idri; Zulfiqar Ali; Sadia Ayub; Edona Jahiu (Journal of Language, Literature, Social and Cultural Studies, 2026)
This paper explores the role of summarizing and paraphrasing in enhancing students' reading skills, particularly through the lens of critical reading. Summarizing involves condensing a text into its main points, while paraphrasing entails restating information in different words without changing the meaning. Both activities require active engagement with texts, encouraging comprehension and analytical thinking. Through a qualitative literature review, this study synthesizes existing research to examine how these activities support reading development. Findings suggest that summarizing and paraphrasing enhance metacognitive awareness, allowing learners to monitor their understanding and improve language proficiency. Additionally, they contribute to better vocabulary use, sentence structure, and information retention. The paper also highlights the strong connection between critical reading and these activities. Summarizing and paraphrasing foster critical thinking skills such as evaluation and synthesis, enabling readers to interpret meaning, assess arguments, and draw conclusions. As a result, students become more reflective and independent readers. The study concludes that incorporating these strategies into reading instruction is essential for promoting comprehension and critical engagement. Educators are encouraged to integrate them into their teaching practices to improve students' academic performance.